Incidence of venous thromboembolism in psychiatric inpatients: a chart review - Takeshima M (Dove Medical Press, 2018)
Masahiro Takeshima,1,* Hiroyasu Ishikawa,1,2,* Kazumi Shimizu,3 Takashi Kanbayashi,1 Tetsuo Shimizu1 1Department of Neuropsychiatry, Akita University Graduate School of Medicine, Akita, Japan; 2Department of Neuropsychiatry, Nakadori Rehabilitation Hospital, Akita, Japan; 3Palliative Care Center, Akita University Hospital, Akita, Japan *These authors contributed equally to this work Purpose: Venous thromboembolism (VTE) is the combination of pulmonary embolism (PE) and deep vein thrombosis. In recent years, VTE has been gaining attention in the field of psychiatry as it can cause sudden deaths in patients hospitalized in psychiatric departments. The purpose of this study was to investigate the incidence of VTE in psychiatric inpatients using contrast-enhanced computed tomography (CT). Patients and methods: At the psychiatric department of the Akita University Hospital, NANOPIA® D-dimer was measured in patients with suspected symptomatic VTE or believed to be at risk for asymptomatic VTE. A follow-up contrast-enhanced CT was also performed in cases of D-dimer values over 1 µg/mL. Patients diagnosed with VTE based on contrast-enhanced CT during hospitalizations between May 1, 2009 and April 30, 2017 were analyzed. VTE incidence was compared in restrained and unrestrained catatonic and noncatatonic patients. We also investigated whether VTE was symptomatic or asymptomatic as well as its outcomes. Results: The overall incidence of VTE was 2.3% (39/1,681) in the 8-year period. VTE was observed in 61.1% (11/18) of catatonic patients, 4.1% (11/270) of noncatatonic restrained patients, and 1.2% (17/1,393) of noncatatonic unrestrained patients. PE was observed in 76.9% (30/39) of VTE patients and 97.4% (38/39) of VTE patients were asymptomatic. Recovery was achieved in all cases of VTE treated with anticoagulation therapy. Conclusion: These results indicate that the risk of VTE is high in psychiatric inpatients and that PE is common in these population. The data may also suggest that contrast-enhanced CT is important in surveying thrombus in suspected cases of VTE. In the psychiatric field, proper attention must be given to VTE, regardless of the presence or absence of catatonia or restraint, particularly given that PE was observed in more than 75% of cases of VTE. Keywords: computed tomography, deep vein thrombosis, D-dimer, psychiatric patients, catatonia, pulmonary embolism